“A Comparative Study Of Risk Assessment Regarding Varicose Veins Among Nurses Working In Critical Care Units And Non-Critical Care Units From The Selected Hospitals In Goa” (International Journal of Food and Nutritional Sciences, 2025)
Introduction: Varicose veins are a common venous disorder among nurses due to prolonged standing, heavy workload, and limited rest. Early symptoms often go unnoticed, increasing progression risk. This study evaluates and compares varicose vein risk among Critical Care and Non-Critical Care nurses while examining demographic and occupational contributors influencing venous health.Methods: A quantitative, descriptive, exploratory design was used among 230 nurses from four multispecialty hospitals in Goa. Convenience sampling included 115 Critical Care and 115 Non-Critical Care nurses. Data were gathered using a risk-factor checklist and Modified VCSS through self-reporting and observation. Analysis employed descriptive statistics, unpaired t-test, ANOVA, and Pearson’s correlation.Results: There was no significant difference in overall risk scores between groups (t=1.49, p>0.05). Marital status, pregnancy history, and constipation showed significant associations with higher risk. Weight and BMI demonstrated weak positive correlations with venous risk, while height showed none. Mild symptoms like pain, heaviness, and burning were most commonly reported.Conclusion: Venous risk among nurses is influenced more by occupational and lifestyle factors than specific work settings. Early symptoms were prevalent across groups, indicating potential progression if unaddressed. Preventive measures including compression therapy, ergonomic adjustments, regular activity, and lifestyle awareness are essential to reduce chronic venous complications and promote vascular health in nursing professionals.